Teacher’s Perception and Practice About Nature-based Teaching at the Pre-primary Level - SHARMA, KRITI (THE PRIMARY TEACHER, 2015)
Young children learn about the natural world by interacting with it, teachers and other adults must attend to the frequency, nature, and the quality of interactions that take place between the children and the natural world during the early years. These days lives of children are much different as they have much lesser opportunities for outdoor free play and contact with the natural world on a regular basis. There are a number of factors which have shrunk their physical boundaries (Francis 1991, Kyttä 2004). Parents these days are afraid for their child’s safety and a ‘culture of fear’ has set in School and teacher’s role is thus imperative in introducing nature to the preschool children. A study was conducted to find out the perception and awareness of teachers towards adoption of nature based education at the pre primary level. Purposive sampling technique was used to select the sample and data was collected with the help of a questionnaire, rating scale and observation schedule. A series of need based workshops creating awareness about nature education was conducted. Findings of the study reveal a positive change in the attitudes and practices of the teachers about natural environment education, on comparison of pre-test and post-test results. The results showed, an exceptional rise in the domain of emotional development, which further proved that, when children develop love for animals, plants, insects, birds and the environment they form a positive attachment to it. This emotional bond aids them in the learning process and thus, facilitates their overall growth or holistic development. Also it implies that the awareness and attitude of teachers can be augmented through intervention programmes. Inclusion of natural environment components in the preschool curriculum needs strengthening.